Provable Submodular Minimization Using Wolfe's Algorithm - Chakrabarty, Deeparnab; Jain, Prateek; Kothari, Pravesh (NIPS'14 Proceedings of the 27th International Conference on Neural Information Processing Systems, Montreal, Canada, 2014)
Owing to several applications in large scale learning and vision problems, fast submodular function minimization (SFM) has become a critical problem. Theoretically, unconstrained SFM can be performed in polynomial time [10, 11]. However, these algorithms are typically not practical. In 1976, Wolfe [21] proposed an algorithm to find the minimum Euclidean norm point in a polytope, and in 1980, Fujishige [3] showed how Wolfe’s algorithm can be used for SFM. For general submodular functions, this Fujishige-Wolfe minimum norm algorithm seems to have the best empirical performance. Despite its good practical performance, very little is known about Wolfe’s minimum norm algorithm theoretically. To our knowledge, the only result is an exponential time analysis due to Wolfe [21] himself. In this paper we give a maiden convergence analysis of Wolfe’s algorithm. We prove that in t iterations, Wolfe’s algorithm returns an O(1/t)-approximate solution to the min-norm point on any polytope. We also prove a robust version of Fujishige’s theorem which shows that an O(1/n2)-approximate solution to the min-norm point on the base polytope implies exact submodular minimization. As a corollary, we get the first pseudo-polynomial time guarantee for the Fujishige-Wolfe minimum norm algorithm for unconstrained submodular function minimization.